2022
DOI: 10.1159/000527029
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Progressive Resistance Training in Parkinson’s Disease: A Systematic Review and Meta-Analysis

Abstract: <b><i>Introduction:</i></b> The aim of this study was to systematically explore progressive resistance training (PRT) effects in Parkinson’s disease (PD). <b><i>Methods:</i></b> Eligible literature was systematically searched from five electronic databases (PubMed, Web of Science, Ovid, Wanfang, and China National Knowledge Infrastructure) from their inception to February 2022. Included studies were selected based on strict eligibility criteria. RevMan 5.3 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the overall QoE was very low due to a high RoB, small sample sizes generating imprecisions across the studies. The moderate to large effect size for strength is in accordance with conclusions of previous reviews applying 'conventional' resistance training programs in neurological populations : stroke injury [SMD = 0.99, CI95% 0.28 to 1.70 Veldema and Jansen (2020); 0.98, 95% CI 0.67 to 1.29, Dorsch et al (2018) 2017)]; PD [1.9, CI95% 0.55 to 3.24, Yang and Wang (2023)].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the overall QoE was very low due to a high RoB, small sample sizes generating imprecisions across the studies. The moderate to large effect size for strength is in accordance with conclusions of previous reviews applying 'conventional' resistance training programs in neurological populations : stroke injury [SMD = 0.99, CI95% 0.28 to 1.70 Veldema and Jansen (2020); 0.98, 95% CI 0.67 to 1.29, Dorsch et al (2018) 2017)]; PD [1.9, CI95% 0.55 to 3.24, Yang and Wang (2023)].…”
Section: Discussionsupporting
confidence: 88%
“…We did not find evidence of superiority of ET over the comparator in improving gait, which is consistent with the findings from previous reviews in neurological populations where either distance or velocity were not better improved after a 'conventional' resistance training program (Braz de Oliveira et al, 2021;Dorsch et al, 2018;Merino-Andres et al, 2022;Veldema & Jansen, 2020). However, a recent review in PD populations reported a better positive effect on a disease-specific impairment: freezing during gait [SMD = 0.55, CI95% 0.16 to 0.95, Yang and Wang (2023)]. We did not retrieve trials assessing changes in freezing in PD, after ET.…”
Section: Discussionsupporting
confidence: 88%
“…Alongside pharmacological treatment, resistance training is often recommended for people with Parkinson’s disease to improve muscle strength and motor function 5 . Traditional resistance training sessions, which often require high training volumes for benefit, can be time-consuming 6 and fatiguing 7 .…”
Section: Introductionmentioning
confidence: 99%